Believing is seeing : creating the culture of art - Staniszewski, Mary Anne. (New York : Penguin, 1995)
Why are the paleolithic Venus of Willendorf, Michelangelo's Sistine Chapel frescoes, and Marcel Duchamp's ready-made urinal all considered works of art? Why, strictly speaking, is a Cindy Sherman photograph more "art-like" than a Da Vinci portrait? How did the painters and sculptors of the Renaissance see their creations? And who decides what art is today? In the tradition of Marshall McLuhan and John Berger, this learned and deliciously subversive book gives us a new way of seeing our artistic heritage. Believing Is Seeing is a work of multicultural scope and glittering intelligence that bridges the gulf between classical Japanese painting and the films of Spike Lee, between high theory and pop culture. Probing beyond the rhetorical surface of standard art histories and drawing on a panoramic array of illustrative material, Mary Anne Staniszewski throws a fresh light on individual works and the often mystifying criteria by which they are valued.
-- What is Art? -- Art and the Modern Subject -- The Term "Art" -- Aesthetics: The Theory of Art -- The Privilege: Creating Ar t -- The Academy -- The Museum -- The Discipline: Art History and The Development of Modernism -- The Avant-Garde, Popular Culture, and the Creation of the Mass Media -- Art and Culture Today.
Includes bibliographical references (pages 303-308).
Keywords: Masterpiece, Artistic; Creation (Literary, artistic, etc.)